1991
DOI: 10.1677/joe.0.1300475
|View full text |Cite
|
Sign up to set email alerts
|

The use of low doses of ACTH in the investigation of adrenal function in man

Abstract: We have investigated the adrenal response, in eight healthy adult men, to low doses of ACTH(1-24) in order to define a dose which will elicit a response similar to that obtained with the short Synacthen test. The studies were performed at 14.00 h and blood samples were withdrawn at 5-min intervals after an i.v. bolus injection of ACTH(1-24). The sampling interval was crucial in determining the timing of the peak response. Using sampling times of 0, 10, 15, 20, 25 and 30 min ensured detection of 47 out of 48 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 13 publications
3
85
0
2
Order By: Relevance
“…We have found that the concentration of ACTH required to obtain the half-maximum cortisol production could vary up to 25-fold depending on the level of cell-to-cell coupling within the cell population. These results provide at least one explanation for the known discrepancy between the Kd value for the interaction of ACTH with its receptor and the ACTH concentrations active on steroidogenesis both in physiological conditions (25,26) and in Cushing's disease (27).…”
Section: Introductionmentioning
confidence: 77%
“…We have found that the concentration of ACTH required to obtain the half-maximum cortisol production could vary up to 25-fold depending on the level of cell-to-cell coupling within the cell population. These results provide at least one explanation for the known discrepancy between the Kd value for the interaction of ACTH with its receptor and the ACTH concentrations active on steroidogenesis both in physiological conditions (25,26) and in Cushing's disease (27).…”
Section: Introductionmentioning
confidence: 77%
“…It has been suggested that the low-dose (0.5-1.0 mg?1.73 m body surface area -2 ) short synacthen test (LDSST) may be more sensitive than the SST in revealing cases of mild adrenal insufficiency [20,25,[28][29][30]. However, ABDU et al [31] found that using the LDSST alone to diagnose adrenal insufficiency lacked specificity with an 11% false-positive rate.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, sensitive tests for assessing adrenal reserve become of significant importance. In recent years, stimulation with low-dose ACTH has been used as a sensitive test to detect subtle changes in adrenal function, which would be missed if the standard ACTH test is used (10)(11)(12). The low-dose ACTH test, following dexamethasone suppression of endogenous ACTH, would therefore be a sensitive method to assess adrenocortical reserve in vivo.…”
Section: Introductionmentioning
confidence: 99%